Case of intra‐abdominal spindle cell tumor after laparoscopic resection of sigmoid colon cancer. Issue 1 (18th January 2016) - Okada, Naoya; Nakamura, Fumitaka; Nanno, Yoshihide; Takada, Minoru; Ambo, Yoshiyasu; Kishida, Akihiro; Kashimura, Nobuichi; Shinohara, Toshiya
Abstract: We herein report a rare case of a patient who developed a spindle cell tumor at the inferior mesenteric artery clipping site. A 58‐year‐old man underwent laparoscopy‐assisted sigmoid colectomy for sigmoid colon cancer. As follow‐up, CT scans were performed every 6 months after the primary surgery. At the 1‐year CT, an nodular soft tissue density mass measuring 54 mm in diameter was found in the mesentery. Although we initially suspected locoregional recurrence of the colon cancer resected 1 year earlier, PET‐CT showed that the tumor was unrelated to the previous cancer. During the subsequent laparotomy, the mass appeared to originate from the inferior mesenteric artery clipping site, and it adhered to the jejunum and the left ureter. We completely resected the tumor and part of the jejunum, which we separated from the abdominal aorta and left ureter. The tumor was histologically diagnosed of a spindle cell tumor. The patient has been free from recurrence since the surgery more than 4.5 years ago. Preoperative PET‐CT was helpful in ruling out local recurrence of colon cancer, which might have made palliative care a better option than surgical resection.